'Let's Talk Autism' –a school‐based project for students to explore and share their experiences of being autistic. Issue 3 (July 2016) - Stevenson, Kathryn; Cornell, Katie; Hinchcliffe, Vivian
Abstract : Understanding what autism means on a personal level can be an important process for young people on the autistic spectrum, and being able to reflect on this and discuss with autistic peers can be particularly helpful. However, opportunities may be restricted by reluctance to talk about diagnosis and because of difficulties in communication inherent in autism. This article describes a therapeutic media project within an ASD school that attempted to support young people to reflect together about what autism meant for them and create resources to share with others. The process is described and main themes of discussions analysed using thematic analysis. Main themes emerged of making sense of diagnosis, experiences of difference and transition to adulthood. Various strategies to manage diagnosis and negotiate identity also emerged. Issues around informed consent and confidentiality and the therapeutic value of such groups are discussed.